A versatile strategy for ultrathin SnS2 nanosheets confined in a N-doped graphene sheet composite for high performance lithium and sodium-ion batteries. Issue 60 (12th July 2018) - Tao, Shi; Wu, Dajun; Chen, Shuangming; Qian, Bin; Chu, Wangsheng; Song, Li
Abstract : Ultrathin SnS2 nanosheets confined in N-doped graphene sheets composite is synthesized by using a simple thermal decomposition method and as excellent electrodes for lithium/sodium-ion batteries. Abstract : In this work, few-layer SnS2 nanosheets confined in a nitrogen-doped graphene sheet composite (SnS2 /NGS) are successfully synthesized via a facile thermal decomposition method. SnS2 /NGS demonstrates sufficient nitrogen-doping and full graphene encapsulation. When evaluated as an anode material for lithium/sodium-ion batteries, it exhibits an excellent electrochemical performance.